Editorial - Montoya-Lerma, James (Revista Colombiana de Entomología, 2019)
Dear Reader,At the RCdE we are committed to improving and innovating, as change is the only constant in research. This is why we will be implementing gradual changes to our journal.From now on, several new aspects will be implemented. First, papers will have a new presentation page that includes the most relevant information about the document and its authors (as in the case of the ORCID). Secondly, editing of each issue will be done continuously, which means that an approved manuscript will be published after it is paid without waiting for the total compilation of the number. Thirdly, we will have a new section entitled “Entomological essays”, the opening of which will be written by Dr. Alejandro Farji-Brener, a recognized authority in the field of insect ecology. We invite you to present your views and collaborate.Also, we invite to the community to be part of the changes we are making visiting http://revistacolombianaentomologia.univalle.edu.co/, in order to gain free access to the new and past publications, all with their DOI assignments. As usual, this issue includes a variety of topics that correspond to the most current national and international entomological research. We hope these changes become a new era in our journal; your contributions and observations are welcome.   James Montoya-Lerma, Ph. D.Editor in chiefRevista Colombiana de Entomología